Evolução setorial e trajetórias tecnológicas em nível de empresas na indústria de celulose e papel no Brasil (1970 - 2004): contexto da política de substituição de importações à competição globalizada - Carvajal García, Claudia Teresa (2006)
Accordingly, a variety of firms's technological capabilities studies, the literature recently is still lacking about the dynamic of sector evolution and technological development in inter-firm and their implication for technical and economical financial performance. More lacking is the research catching up the evolution of industrial sectors after the institutional reforms in the 90. For that, the focus of the dissertation is to analyze the main of the evolution of the pulp and paper industry from 1970 to 2004, using as reference points the import-substitution policy and the economic deregulation of the 1990s. Futhermore, the work tries to evaluate how such changes at industry level have been perceived from a firm point of view in terms of accumulation of technological capabilities and improvement of economic financial performance. This linkage is tested and examined in the following firms: Aracruz (Barra do Riacho establishment ), Klabin (Monte Alegre establishment) e Votorantim Celulose e Papel ¿ VCP (Jacareí establishment), defining the same time period of sectoral level. As far as the industry level study is concerned, it is based on the average rate of annual growth of some selected variables, given that the technological capabilities test is performed according to the methodology already existing in the literature, but properly adapted to the pulp and paper case. Similarly, the analysis regarding the improvement of the economic financial performance is based on a set of industry specific indicators. Hence, the work is built upon multiple case studies, taking into account both the qualitative and quantitative evidence, i.e. interviews, direct observations, as well as firm reports. Finally, it is worth emphasizing as the analysis of the changes in the sector, in conjunction with the above mentioned methodology used to measure the technological capabilities in the context of an evolving industrial regime, is still lacking in emerging economies as well as in Brazil. According to the empirical evidence, the reforms of the 1990s had a positive impact on the industrial development, from both the national and international viewpoint. Such a transformation was evident at firm level in terms of accumulation of technological capabilities and improvement of economic financial indicators. Indeed, the results show that the speed of accumulation of technological capabilities within the firms influences positively the performance indicators. On the other hand, these are also related to external factors, such as the macroeconomic conditions, which as such have not been considered in details.